If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + -2(3w + -2t) = 2t + 9 Reorder the terms: t + -2(-2t + 3w) = 2t + 9 t + (-2t * -2 + 3w * -2) = 2t + 9 t + (4t + -6w) = 2t + 9 Combine like terms: t + 4t = 5t 5t + -6w = 2t + 9 Reorder the terms: 5t + -6w = 9 + 2t Solving 5t + -6w = 9 + 2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2t' to each side of the equation. 5t + -2t + -6w = 9 + 2t + -2t Combine like terms: 5t + -2t = 3t 3t + -6w = 9 + 2t + -2t Combine like terms: 2t + -2t = 0 3t + -6w = 9 + 0 3t + -6w = 9 Add '6w' to each side of the equation. 3t + -6w + 6w = 9 + 6w Combine like terms: -6w + 6w = 0 3t + 0 = 9 + 6w 3t = 9 + 6w Divide each side by '3'. t = 3 + 2w Simplifying t = 3 + 2w
| 8y=-64x+16 | | 5(3w-2)-7=23 | | x-x*0.2765=1200 | | 3(2z+1)=35 | | 7p^2=-36p-5 | | -2a+5+3a=14-21 | | x-x*0.2765=1000 | | x*2x=64 | | x^2-34*x+342=0 | | 5x^2+5x-30=0 | | x-x*0.2765=110 | | 6z-3=z+27 | | 1/5(10-15x)+4=2 | | 1/5(10-15x)+=2 | | x-x*0.2765=180 | | 3x-5x=19 | | -12-5= | | (x^6+64)=0 | | 75a=75*2 | | 4x-2=9+6x | | 5z-4=16 | | 7-3x=8x-4 | | J+4y=xm | | 3(4y-1)=6y | | 4(x+1.1)=3x+6.8 | | 2+3a=17 | | 3a+3=15 | | 2a+7=13 | | 8(x+1)=2(x+2) | | 5x+3=4x-6 | | 6a-12=48 | | A-5=5-5 |